The SMILE AND ITS DIMENSIONS - Londoño-Bolívar, Miguel Ángel; Botero-Mariaca, Paola (Revista Facultad de Odontología Universidad de Antioquia, 2012)
The purpose of this review is to present the emerging findings on the potential anti-cariogenic properties of the bioactive molecules of oral metabolism related with ammonia production. The literature analysis supports a new preventive dimension in the knowledge of dental caries disease by studying the published evidence provided by in vitro and clinical studies, in which the ammonia produced from urea and arginine in the oral environment represents an important endogenous inhibitory factor in the development of dental caries lesions. This fact would support the hypothesis that ammonia production by urease and the arginine deiminase system could potentially inhibit the development of dental caries by neutralizing acids and stabilizing the oral microbiota, thus enhancing the conditions for oral health maintenance. This review presents studies on the oral enzyme activity which may constitute a promising field in the definition of new lines of research in cariology, particularly in vivo and in situ, a med at establishing the effectiveness and clinical application of these compounds in the prevention of dental caries.